The British Academy’s home at 10-11 Carlton House Terrace: a history - Whyte, W (British Academy, 2024)
Built on the site of a princely palace and intended to house aristocrats in almost equally impressive accommodation, Carlton House Terrace is in many respects an unlikely home for a learned society. This article traces the history of two houses: numbers 10 and 11, exploring their architecture and the lives of those who occupied them from their construction in the early 19th century until the present day. It seeks to show how shifting fashions and changing functions shaped the fabric that we now encounter. This building biography reveals a palimpsest in which each generation has reinvented the site—a process that continues with the recent work to refurbish the basement and open the British Academy’s home to the public. The text is accompanied by an Appendix of Plates.